Tracking the influence of a very close secondary star on planetary growth and evolution - Camargo, B. C.B. [UNESP]; Moraes, R. A.; Winter, O. C. [UNESP]; Foryta, D. W. (Oxford University Press (OUP), 2024)
This work investigated the dynamics of planets in binary systems and provided insights into the stability and evolution of these systems. We explored the influence of a nearby secondary star on planetary growth and evolution, focusing on S-type configurations. We tracked the orbits of the planets and analysed their stability over long time-scales, considering various parameters such as mass, eccentricity, and inclination. Our results show that the presence of a secondary star can significantly impact the growth and evolution of planets, leading to changes in their orbits and potential ejection from the system, however, it was possible to identify stable planets even in systems experiencing multiple disturbances. One of the most significant results of the work was the analysis of the increased material in the disc near the primary star, which contributes to planet growth, driven by the density spirals influenced by the binary star. These findings have important implications for the search for habitable exoplanets and emphasize the need for further studies of planetary systems in binary star environments.
Keywords: binaries: close; exoplanets; hydrodynamics; planets and satellites: dynamical evolution and stability; protoplanetary discs